Predictors of preterm neonatal mortality in the neonatal intensive care unit at a tertiary medical institution in Ethiopia - Feleke, Tihun; Kaweti, Gudeta (Frontiers in Pediatrics, 2025)
BackgroundPremature death is a serious health concern in developing countries, including Ethiopia.MethodsA retrospective cohort study was conducted in Hawassa University Comprehensive Specialized Hospital from 9 May 2019 to 22 April 2021. A total of 723 preterm neonates were enrolled in this study. The Kaplan–Meier survival curve was used to calculate the survival rate. The Cox proportional hazard ratio was used to evaluate the relationship between the dependent and independent variables. A 95% confidence level was used to check for significance.ResultsPreterm neonatal mortality accounted for 33.3% of neonatal admissions. Early neonatal sepsis [adjusted hazard ratio (AHR) = 1.34; 95% CI: 1.003, 1.79], a 5-min Apgar score of less than 7 (AHR = 1.73; 95% CI: 1.17, 2.55), perinatal asphyxia (AHR = 2.25; 95% CI: 1.67, 3.02), and recent multiple pregnancies (AHR = 1.66; 95% CI: 1.22, 2.26) were predictors of preterm neonatal mortality.ConclusionEarly breastfeeding, prevention and early treatment of perinatal hypoxia and neonatal infections, identification, and monitoring of multiple pregnancies could help to reduce preterm neonatal mortality.